The Lost SYMBOL - Brown, Dan, 1964-, (Corgi Books, 2015)
ADVENTURE / THRILLER. Robert Langdon flies to Washington after an urgent invitation to speak in the Capitol building. The invitation appears to have come from a friend with copper-bottomed Masonic connections, Peter Solomon. But Langdon has been tricked: Solomon has, in fact, been kidnapped, and (echoing the grisly opening of the last book) a macabre mutilation plunges Langdon into a tortuous quest. His friend's severed hand lies in the Capitol building, positioned to point to a George Washington portrait that shows the father of his country as a pagan deity. The ruthless criminal nemesis here is another terrifying figure in Brown's gallery of grotesques: Mal'akh, a powerfully built eunuch with a body festooned with tattoos. Mal'akh is seeking a Masonic pyramid that possesses a formidable supernatural power, and a pulse-pounding hunt is afoot, with Langdon stalled rather than aided by the CIA.